The role of strategic planning in relationship marketing - BONDREA, Aurelian A.; GÂRDAN, Daniel Adrian; GEANGU, Iuliana Petronela (Annals of Spiru Haret University. Economic Series, 2010)
The evolution of relationship marketing has been one of the most talked about, partly because it not only proposed a radical change at the very beginning of the marketing action and philosophy, but also because of its complexity. Among many different issues regarding the relationship marketing, the one referring to the strategic planning process has been very little dealt with among the marketing specialists. The present article discusses this sensitive matter and represents a short insight into this complex dilemma: is planning possible or not when talking about commitment, trust, harmony, empathy with the consumer on a regular basis, during a lifetime relationship?